Assessment of the Effect of Intravenous Pamidronate in the Treatment of Legg-Calve-Perthes Disease in Children - Shashaani, Niloofar; Shiari, Reza; Sami, Hossein; Rahmani, Khosro; Hajipour, Mahmoud; Javadi Parvaneh, Vadood; Mirzaee, Azadeh Zeinab (Novelty in Biomedicine, 2024)
Background: Legg-Calvé-Perthes disease (LCPD) presents in childhood with idiopathic avascular necrosis of the femoral head(s), which can lead to disability and the need for corrective surgery at an early age. Bisphosphonates are a group of drugs that prevent osteoclastic bone resorption and may be helpful in the treatment of LCPD. So far, no trial has been conducted to investigate the effect of monthly intravenous pamidronate in the treatment of LCPD in children. Therefore, we assessed this issue in this study. Materials and Methods: This study was conducted as a clinical trial on children with LCPD who were referred to Mofid Children's Hospital (Iran-Tehran) during 2022 and 2023. Pamidronate was injected monthly and intravenously at a dose of 1 mg/kg/dose. Both groups were the same in terms of the type of treatment received (except pamidronate), the number of visits, and other follow-up parameters. The study was conducted for one year. The significance level was considered less than 0.05. Results: Forty-seven patients were included in the study. Twenty-one (60%) were in the pamidronate group, and 26 (40%) were in the control group. The mean age in the intervention group was 6.19 ± 1.69 years, and it was 6.15 ± 1.85 years in the control group (P-value=0.944). There was no statistically significant difference in children's gender (P-value = 0.731). Patients with pamidronate had a better overall score than the control group. The overall score in the pamidronate group was 2.37 more than the control group, but this difference was not statistically significant (P value=0.753). The scores of pain, lameness, walking, distance, squat, cross leg, and range of motion (ROM) in the pamidronate group were not significantly different from the control group (P value>0.05). Conclusion: Pamidronate can improve the clinical results of children with Legg-Calve-Perthes disease, and it is recommended that this drug be used along with the usual treatments for these patients.